Grafos e seu polinômio característico - Rossini, Gustavo Feltrin (2017)
In this work, a theme related to social networks was used as a didactic strategy to connect conceptual and theoretical mathematics to the daily life of high school students. This study was applied as a workshop at the 15th Semana Acadêmica Integrada do Centro de Ciências Naturais e Exatas. From the motivating problem in the field of Graphs, matrices were genereated, calculating the determinants by the Laplace and Scheduling methods, and then determining the roots of the characteristic polynomial by radicals. The subject of complex numbers is also approached. Finally, as a complement to theory and as a usage suggestion of information technologies in the teaching-learning process, use is made of the Geogebra software. It is believed that the material produced can serve both as a theoretical and a motivational reference for teachers who work in High Schools.